Limitations on Community Participation in Planning Decision-making in Peninsular Malaysia: A Review of Recent Studies - Khalid, Zanudin; Ibrahim, Ngah; Siti Hajar, Misnan (SPSD Press, 2019)
Community participation in planning decision-making in Peninsular Malaysia is fundamental for achieving sustainable development by deliberating on the present and future interests of the community. The provision for the community to participate in both the strategic and operational planning is stated in the Town and Country Planning Act 1976 (Act 172). Community participation in the planning process helps decision-makers to make better decisions by incorporating the community’s experiential knowledge into the process. Furthermore, it is meant to promote greater citizenship and to democratise governance through the involvement of multiple stakeholders. Nevertheless, the current state of community participation in planning decision-making in Peninsular Malaysia indicates shortcomings, hence impeding the effort to achieve its primary purpose. This paper attempts to explore the lack of community participation based on its current state. The inadequacies of the conventional participatory process employed by local planning authorities in Peninsular Malaysia are elucidated by reviewing previous studies conducted by Malaysian scholars. The issues that transpire from the literature review are sorted into operational, structural, and cultural aspects. This study concludes that the current community participation in planning decision-making in Peninsular Malaysia points to the ineffectiveness of the process, thus hindering the ability of the community to access a genuine participation avenue.